Pengaruh Literasi Keuangan dan Kemudahan Pengguna Terhadap Keputusan Menggunakan QRIS dalam Pembayaran Retribusi di UPTD Pengujian Kendaraan Bermotor Kota Denpasar - Putu Ayu Windarmayanthi; I Wayan Sudiana; Putu Nuniek Hutnaleontina (UNHI Press, 2025)
The Motor Vehicle Testing Technical Implementation Unit (UPT PKB) of Denpasar City ensures vehicle safety through rigorous inspections. Governed by Denpasar City Regional Regulation Number 20 of 2011, the unit's financing comes from motor vehicle levies. To enhance service efficiency, the UPT PKB adopted QRIS for non-cash levy payments, increasing Regional Original Income (PAD) despite challenges in technological adaptation and social changes. This study investigates how financial literacy and ease of use influence the decision to use QRIS for paying levies at the UPTD Denpasar City Motor Vehicle Testing. The research involved 28,190 mandatory vehicle tests using QRIS, employing purposive sampling and multiple linear regression analysis. Findings reveal that financial literacy and user convenience positively and significantly impact the decision to use QRIS for levy payments at the UPTD Denpasar City Motor Vehicle Testing.